Visual data and their use in science education - Finson, Kevin D.; Pedersen, Jon E. (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
Visual Data in Science Education builds upon previous work done by the editors to bring some definition to the meaning of visual data as it relates to education, and highlighted the breadth of types and uses of visual data across the major academic disciplines. In this book, the editors have brought this focus specifically to science education through the contributions of colleagues in the field who actively research about and engage in teaching with visual data. The book begins by examining how the brain functions with respect to processing visual data, then explores models of conceptual frameworks, which then leads into how related ideas are actuated in education settings ranging from elementary science classrooms to college environments. As a whole, this book fosters a more coherent image of the multifaceted process of science teaching and learning that is informed by current understandings of science knowledge construction, the scientific enterprise, and the millennium student as they relate to visual data.